CLEANER PRODUCTION OF ETHANOL FUEL IPOMOEA BATATA (POTATO) AND ITS IMPACT ON ACCOUNTING RESERVE ENERGY AND SUSTAINABLE DEVELOPMENT OF PERU - Anaya M., Fernando (2008)
The goal of this research work is the design of a cleaner process for the production of fuel ethanol sweet potato. Applying the principles of conceptual design, Pinch analysis and the use of simulators chem cad and pinch cad, it is determined that the process with molecular sieves is the most effective to get ethanol from 99.5% purity with a power demand of 1400 Kj/kg of ethanol. We conclude that these results impacting positively on the economy of Peru by establishing a path of sustainable development both technically, economically, socially and environmentally.